2021
DOI: 10.1111/jgh.15696
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of oral sulfate solution versus polyethylene glycol–ascorbic acid for bowel cleansing in elderly people

Abstract: Background and Aim:The efficacy and safety of the recently introduced low-volume purgatives in elderly people are not well known. Therefore, in this trial, we aimed to evaluate and compare the efficacy of two low-volume agents, oral sulfate solution (OSS) and 2-L polyethylene glycol with ascorbic acid (PEG-Asc), in elderly people. Methods: A prospective, randomized, single-blinded, multicenter, non-inferiority trial was performed at three university-affiliated hospitals in South Korea. Outpatients aged 65-80 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…Seven studies 20,44–49 blinded investigators but not participants and were therefore judged as unclear risk in performance bias except for one study, 43 which did not blind either investigators or participants. Regarding outcome assessment, five studies 20,43,45,46,49 were judged as low risk of bias because it was evaluated by ether blinded independent trained central readers or blind investigators; however, another three studies 44,47,48 did not clearly describe detailed information on outcome assessment and were therefore rated as unclear risk. For the remaining items, all RCTs were considered as low risk.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies 20,44–49 blinded investigators but not participants and were therefore judged as unclear risk in performance bias except for one study, 43 which did not blind either investigators or participants. Regarding outcome assessment, five studies 20,43,45,46,49 were judged as low risk of bias because it was evaluated by ether blinded independent trained central readers or blind investigators; however, another three studies 44,47,48 did not clearly describe detailed information on outcome assessment and were therefore rated as unclear risk. For the remaining items, all RCTs were considered as low risk.…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of a previous meta‐analysis, 23 OSS would increase the detection of polyps and adenomas because it significantly increased the proportion of patients with excellent bowel preparation. However, among the included six RCTs that reported primary outcomes, only one found a significantly increased PDR 20 or ADR 47 in the OSS group. The other included RCTs did not detect differences between OSS and PEG‐based regimens in terms of PDR or ADR, which were consistent with the results of a retrospective study 41 and a conference abstract 50 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An inadequate bowel preparation regimen is an important factor that affects the adequacy of bowel preparation. It is reported that the rate of inadequate bowel preparation ranges from 20 to 30% (6). Therefore, it is crucial to improve the preparation adequacy rate.…”
Section: Introductionmentioning
confidence: 99%